Experiences of being a therapy radiographer - Heather Lawrence; Marie Poggenpoel; Chris Myburgh (AOSIS, 2011)
The purpose of this research was to explore and describe how therapy radiographers experience their profession. A qualitative, exploratory, descriptive and contextual design was utilised. The purposive sample consisted of 14 therapy radiographers employed at an academic hospital in Gauteng, South Africa. Data were collected using focus group interviews until data saturation was achieved. An appreciative inquiry interview technique was utilised, and data analysis was conducted by open coding to identify themes. Themes that were identified were life-giving forces that promote personal and professional engagement resulting in a sense of purpose; professional stagnation; and facilitating change through harnessing positive energy and commitment for change. Opsomming Die hoofdoel van hierdie navorsing is om te verken en beskryf hoe radioterapeute hulle beroep beleef. 'n Kwalitatiewe, verkennende, beskrywende en kontekstuele navorsingsontwerp is gebruik. Die doelgerigte steekproef het bestaan uit 14 radioterapeute werksaam by 'n akademiese hospitaal in Gauteng, Suid Afrika. Data is met behulp van fokusgroep onderhoude ingesamel totdat dataversadiging bereik is. 'n 'Appreciative inquiry' onderhoudstegniek is gebruik met die stel van vrae, en data analise is met behulp van oop kodering gedoen om temas te identifiseer. Die temas wat geidentifiseer was is lewensgewende magte wat persoonlike en professionele betrokkenheid bevorder wat 'n singewing tot gevolg het; professionele stagnering; en fasilitering van verandering deur die gebruikmaking van positiewe energie en toewyding vir verandering.